Effectiveness of Implementing Corporate Social Responsibility (CSR) towards the Community (Case Study at CV Mekar Abadi Wonosobo) - Ismanudin, Ismanudin (Jurnal Daulat Hukum, 2024)
This research aims to investigate the implementation of Corporate Social Responsibility (CSR) at CV Mekar Abadi using an approach of three main theories: legal effectiveness, management and Islamic business ethics. The main objective is to gain an in-depth understanding of the company's CSR practices and identify relevant barriers and solutions in the context of the wood industry. The research method used involved a field study approach with interviews and observations at CV Mekar Abadi. In addition, literature studies are used to support the identification of a conceptual framework in analyzing the company's CSR implementation. This triangulation approach allows researchers to gain a holistic and in-depth understanding of a company's CSR practices. The research results show that CV Mekar Abadi faces a number of challenges, including price fluctuations and market instability in the wood industry. Even though companies have managed to survive the COVID-19 pandemic, the impact of policy changes related to the pandemic has become an additional obstacle in implementing broader CSR programs. In overcoming these challenges, the proposed solutions include increasing transparency, developing inclusive CSR programs, and in-depth understanding of Islamic business ethics. The research conclusions emphasize the importance of adapting CSR according to the business context and provide useful recommendations for similar companies facing similar challenges.